DETERMINAN PENGGELAPAN PAJAK - Claudio Abineno; Mila Susanti (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
A Tax revenue is the largest source of state income used to carry out government work programs. But the phenomenon of tax evasion still occurs due to negligence and lack of literacy about tax rules and supervision from tax authorities. Therefore, this study aims to determine the factors that cause tax evasion carried out by tax subjects. This study used primary data through the distribution of questionnaires to respondents as tax subjects. The quantitative data is processed using causal associative methods. The results showed that understanding, justice, sanctions and the tax system had a significant effect on tax evasion both partially and simultaneously.